2018
DOI: 10.1080/08927014.2018.1539707
|View full text |Cite
|
Sign up to set email alerts
|

Living on the edge: biofilms developing in oscillating environmental conditions

Abstract: For the first time, densities and diversity of microorganisms developed on the ocean glider were investigated using flow cytometry and Illumina MiSeq sequencing of 16S and 18S rRNA genes. Ocean gliders are autonomous buoyancy-driven underwater vehicles, equipped wi th sensors continuously recording physical, chemical, and biological parameters. Biofilms on the glider were exposed to periodical oscillations of salinity, oxygen, temperature, pressure, depth and light, due to periodic ascending and descending of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 55 publications
(59 reference statements)
2
25
0
Order By: Relevance
“…In contrast, chitosan paints significantly reduced densities of micro-fouling on the surface of a sea glider exposed to periodical oscillations of environmental conditions in the Sea of Oman. Moreover, it was found that the structure of microbial communities formed on chitosan paints were similar to unprotected surfaces and were totally different from what is found on surfaces coated with copper-based antifouling paints, suggesting that chitosan-based coatings have minimal negative impact on marine communities [131].…”
Section: Antifouling Paints and Coatingsmentioning
confidence: 88%
“…In contrast, chitosan paints significantly reduced densities of micro-fouling on the surface of a sea glider exposed to periodical oscillations of environmental conditions in the Sea of Oman. Moreover, it was found that the structure of microbial communities formed on chitosan paints were similar to unprotected surfaces and were totally different from what is found on surfaces coated with copper-based antifouling paints, suggesting that chitosan-based coatings have minimal negative impact on marine communities [131].…”
Section: Antifouling Paints and Coatingsmentioning
confidence: 88%
“…We observed a similar taxonomic shift with a progressive increase of Proteobacteria abundance (particularly Gammaproteobacteria). Marine biofilm communities are selected from planktonic communities but appear to be dissimilar from them (Lee et al, 2008;Briand et al, 2012;Dobretsov et al, 2018). These differences could also be due to the distinct structures between the complex and organized cellular of biofilms and of individual, planktonic cells which are present in the water column (Doghri et al, 2015).…”
Section: Taxonomy Of Biofilms On Plates With Anti-corrosion Paint Andmentioning
confidence: 99%
“…Planctomycetes (classes of BD7-11 and OM190) that were found abundant in the biofilms sampled from all three surface types (>2.5%) in this study, have also been previously recorded on fouling control surfaces (Leary et al ., 2014; von Ammon et al ., 2018; Ding et al ., 2019), although this phylum is underestimated by previous NGS biofilm studies on fouling control coatings (e.g. Muthukrishnan et al ., 2014; Briand et al ., 2017; Flach et al ., 2017; Hunsucker et al ., 2018; Winfield et al ., 2018; Dobretsov et al ., 2019). Although not frequently reported, Verrucomicrobia has also been found in fouling control studies (Leary et al ., 2014; Winfield et al ., 2018), and was confirmed to be abundant in all three coating treatments (>1.8%) in this study.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a handful of studies have reported the application of next generation sequencing (NGS) techniques to investigate the response of marine biofilm community profiles developed on marine fouling control coatings (Muthukrishnan et al ., 2014; Leary et al ., 2014; Briand et al ., 2017; Flach et al ., 2017; Hunsucker et al ., 2018; Winfield et al ., 2018; von Ammon et al ., 2018; Dobretsov et al ., 2019; Ding et al ., 2019). NGS technology based on sequencing ribosomal RNA genes, is appropriate for a range of applications including highly diverse community analysis, while offering large volume of data that allow for statistical testing (Fukuda et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation